Power in numbers. Drivers of high population density in insular lizards. Issue 1 (18th October 2015) - Novosolov, Maria; Rodda, Gordon H.; Feldman, Anat; Kadison, Amy E.; Dor, Roi; Meiri, Shai
Abstract: Aim: Islands organisms usually have fewer predator and competitor species than mainland ones. This is thought to result in high population densities on islands. We hypothesize that insular lizards have denser populations than mainland species and that density, in general, is negatively correlated with competitor and predator richness. Location: Global. Methods: We compared densities of 346 lizard species on islands and the mainland while examining the relationship between density and, predator and competitor richness, primary productivity, seasonality and island area. We controlled for phylogenetic non‐independence, body mass and study area, which are known to strongly affect population density. Results: Insular populations (especially on snake‐free islands) are denser than mainland ones. Mainland populations of lizard species that also inhabit islands were denser than those of species that do not inhabit islands. Population density was the highest on islands with low net primary productivity and was not significantly affected by competitor or predator richness. Moreover, insular populations show high density regardless of island area. Main conclusions: We conclude that the ability of mainland species to reach high population densities may increase their chances in reaching and successfully colonizing islands. We postulate that population density may be affected by predator and competitor density rather than by their richness. Density increase on islands may result not from the environmental simplicity of island faunas but through propagule sorting or pressure.